2016
DOI: 10.1111/ina.12308
|View full text |Cite
|
Sign up to set email alerts
|

The impact of particle filtration on indoor air quality in a classroom near a highway

Abstract: A pilot study was performed to investigate whether the application of a new mechanical ventilation system with a fine F8 (MERV14) filter could improve indoor air quality in a high school near the Amsterdam ring road. PM10, PM2.5, and black carbon (BC) concentrations were measured continuously inside an occupied intervention classroom and outside the school during three sampling periods in the winter of 2013/2014. Initially, 3 weeks of baseline measurements were performed, with the existing ventilation system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…9,10 Recently, data related to IAQ in schools were collected in different European countries [11][12][13][14] and several studies have shown that children who study and live in industrial areas have a tendency to present increased respiratory symptoms when compared to those living in other areas. 17 Many of the more common indoor sources, such as smoking and cooking, are usually not present in school buildings, but several studies have demonstrated that exposure to airborne particles in classrooms can be high anyway, [18][19][20][21] also including increased airborne bacterial concentration in respirable particulate matter. Schools are places with a high population density, in which different types of pollutants may be introduced and remain for a long time due to insufficient outside air supply, and are often characterized by infrequent interventions for environmental remediation and building maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Recently, data related to IAQ in schools were collected in different European countries [11][12][13][14] and several studies have shown that children who study and live in industrial areas have a tendency to present increased respiratory symptoms when compared to those living in other areas. 17 Many of the more common indoor sources, such as smoking and cooking, are usually not present in school buildings, but several studies have demonstrated that exposure to airborne particles in classrooms can be high anyway, [18][19][20][21] also including increased airborne bacterial concentration in respirable particulate matter. Schools are places with a high population density, in which different types of pollutants may be introduced and remain for a long time due to insufficient outside air supply, and are often characterized by infrequent interventions for environmental remediation and building maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Schools are places with a high population density, in which different types of pollutants may be introduced and remain for a long time due to insufficient outside air supply, and are often characterized by infrequent interventions for environmental remediation and building maintenance. 17 Many of the more common indoor sources, such as smoking and cooking, are usually not present in school buildings, but several studies have demonstrated that exposure to airborne particles in classrooms can be high anyway, [18][19][20][21] also including increased airborne bacterial concentration in respirable particulate matter. 22 The presence of outdoor pollution sources-such as vehicles, industrial complexes, petrochemical plants, gas/oil stations, and commercial facilities-in the proximity of school buildings may represent an important health risk factor, in particular for vulnerable individuals such as children.…”
Section: Introductionmentioning
confidence: 99%
“…and human activities (e.g., open windows and use of fan, air purifier, or air conditioning). 2,4,5 However, examination of various methods and results suggest that a mass balance approach that uses reliable estimates of infiltration and includes detailed information about individual homes is not available. 6 As the exposure error associated with poorly characterized infiltration was found to bias health effects assessment, the statistical power of epidemiological studies to detect health effects of exposure to indoor air pollutants remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, household income did not have a significant association with attending a school or daycare within one block of a roadway with moderate to heavy traffic, and little variation was observed between cities. Concerns over potential health effects in children and youth have led to recent investigations of possible interventions to reduce exposure to TRAP in schools (MacNeill et al 2016 , van der Zee et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%